(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
Maqsud was the eldest child of her parents. His family had four more children after him. These are Maqsud, Safura, Fuod, Nozim and Saida. Father Masim the father was a man who was extremely interested in literature and poetry, and was a doctor by profession. Аbout the life and work of Maqsud Shaykhzoda, about his entry into Uzbekistan and acquaintance with the famous writers here, about his creations during the war years